Evaluation of Hair Characteristics and Animal Age on the Impact of Hair Cortisol Concentration in Feedlot Steers - Baier, Faith; Grandin, Temple; Engle, Terry; Edwards-Callaway, Lily (Frontiers in Veterinary Science, 2019)
Hair cortisol is a novel biomarker of chronic stress. The objective of this study was to determine the effect of hair color and length, as well as, animal age on hair cortisol concentration in beef feedlot steers. Nineteen beef crossbred steers used for nutrition research and housed in a small feedlot setting were used for this study. Seven of the steers (473 ± 3.1 kg; approx. 9 years of age) were fitted with ruminal fistulas and duodenal cannulas. The other twelve steers (308 ± 2.0 kg; approx. 2.5 years of age) were fitted with only ruminal fistulas. Hair samples from each steer were collected throughout a period of six weeks from six different areas and analyzed for cortisol concentrations. One pre-determined area was shaved each week for five weeks (Weeks 1-5). During week six, all five, previously shaved areas and an additional area was shaved to collect hair samples of various lengths. Hair length was recorded prior to the collection of each hair sample. Only data from the last week (Week 6) of collection were included in the analyses. Steers were categorized into one of three groups: old with black hair (OB, n = 3); old with white hair (OW, n = 3); young with black hair (YB, n = 12). Older steers exhibited greater hair cortisol concentrations than younger steers (P < 0.001). Hair cortisol concentration was not impacted by duration of growth (P = 0.33). Cortisol concentrations exhibited a weak, positive correlation with hair length (r = 0.33, P-value = 0.01). The average hair growth per week of beef steers in the winter months was calculated to be 0.90 mm. Further research should be performed to improve our understanding of the effect of hair characteristics, sampling methodologies and analysis techniques on hair cortisol concentrations.